THE EFFECT OF ESG DISCLOSURE ON EQUITY VALUATION WITH PROFITABILITY AS A MEDIATING VARIABLE - Nurul Annur; Sutisna; Gema Ika Sari (International Journal Management and Economic, 2026)
The mining sector in Indonesia exhibits a disparity between corporate profitability and equity valuation, indicating that non-financial factors may influence investors’ assessments. This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure on equity valuation with profitability as a mediating variable. The research sample consists of mining companies listed on the Indonesia Stock Exchange during the 2020–2024 period. A quantitative approach with panel data regression analysis was employed. Data were collected from companies’ annual and sustainability reports and analyzed using EViews software. The results indicate that Environmental and Social Disclosure have no significant effect on equity valuation, while Governance Disclosure has a positive and significant effect. Environmental Disclosure negatively affects profitability, whereas Social and Governance Disclosure positively and significantly influence profitability. Profitability has a positive and significant effect on equity valuation but does not mediate the relationship between ESG disclosure and equity valuation. Simultaneously, ESG disclosure significantly affects both profitability and equity valuation. This study concludes that good corporate governance plays a crucial role in enhancing equity valuation, while environmental and social disclosures require further strengthening to generate optimal financial and market value impacts.